Science interests of grades five and six children of the University of the Philippines Elementary School - Najera, Paz (Ayson) 1909- (s.n.], 1964)
This study was based on the belief that a sound curriculum should have, as one of its bases, the science interest of the children for whom the curriculum is to serve. The study identifies the science interests of the children of the University of the Philippines Elementary School.